Effect of the amount of intraoperative fluid administration on postoperative pulmonary complications following anatomic lung resections - KARARMAZ, ALPER; BİLGİLİ, BELİZ; YILDIZELİ, BEDRETTİN; BEKİROĞLU, GÜLNAZ NURAL; BATIREL, HASAN FEVZİ; CİNEL, İSMAİL HAKKI; BOSTANCI, KORKUT; ARSLANTAŞ, MUSTAFA KEMAL (MOSBY-ELSEVIER, 2015)
Objective: Excessive fluid administration during lung resections is a risk for pulmonary injury. We analyzed the effect of intraoperative fluids on postoperative pulmonary complications (PCs). Methods: Patients who underwent anatomic pulmonary resections during 2012 to 2013 were included. Age, weight, pulmonary function data, smoking (pack-years), the infusion rate and the total amount of intraoperative fluids (including crystalloid, colloid, and blood products), duration of anesthesia, hospital stay, PCs, and mortality were recorded. PCs were defined as acute respiratory distress syndrome, need for intubation, bronchoscopy, atelectasis, pneumonia, prolonged air leak, and failure to expand. Univariate analyses and multivariate logistic regression were performed. A Lowess curve was drawn for intraoperative fluid threshold. Results: In 139 patients, types of resections were segmentectomy-lobectomy (n = 69; extended n = 37; video-assisted thoracoscopic surgery n = 19) and pneumonectomy (n = 9; extended n = 5). One hundred sixty-one PCs were observed in 76 patients (acute respiratory distress syndrome [n = 5], need for intubation [n = 9], atelectasis [n = 60], need for bronchoscopy [n = 19], pneumonia [n = 26], prolonged air leak [n = 19], and failure to expand [n = 23]). Overall mortality was 4.3% (6 out of 139 patients). Mean hospital stay was 8.5 +/- 4.8 days. Univariate analyses showed that smoking, intraoperative total amount of fluids, crystalloids, blood products, and infusion rate as well as total amount of crystalloids and infusion rate during the postoperative first 48 hours were significant for PCs (P = .033, P < .0001, P = .001, P = .03, P < .0001, P = .002, and P < .0001, respectively). In multivariate logistic regression analysis intraoperative infusion rate (P < .0001) and smoking were significant (P = .023). An infusion rate of 6 mL/kg/h was found to be the threshold. Conclusions: The occurrence of postoperative PCs is seen more frequently if the intraoperative infusion rate of fluids exceeds 6 mL/kg/h.
Keywords: RESPIRATORY-DISTRESS-SYNDROME; THORACIC-SURGERY; RISK-FACTORS; INJURY; MANAGEMENT; MORTALITY; CANCER; MORBIDITY; THERAPY; IMPACT